2018
DOI: 10.24071/llt.2018.210203
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This research was conducted to examine Indonesian students' experiences in using technology in learning English outside the classroom with regards to learner autonomy as an important capacity for students' learning success. The subjects of the study were students of a private Senior High School in South Tangerang. As for the methodology, this research applied quantitative and qualitative design. Quantitative elements include questionnaires as the data collecting method, while qualitative elements used semi str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…The findings concerning the smartphone apps the participants in this research reported using when engaging in literacy practices to improve their English during the COVID-19 crisis correspond with results from Alrefaai (2019) and Al Mukhallafi (2019), who reported that students at universities in Saudi Arabia have a positive attitude towards using mobile apps to learn English. The digital literacy practices of college students mostly involved using smartphones and this result is consistent with results by Warni, Abdul Aziz and Febriawan (2018), who mentioned that students in Indonesia use mobile phones in their everyday lives to learn English outside the classroom.…”
Section: Improving Competency In Englishsupporting
confidence: 87%
“…The findings concerning the smartphone apps the participants in this research reported using when engaging in literacy practices to improve their English during the COVID-19 crisis correspond with results from Alrefaai (2019) and Al Mukhallafi (2019), who reported that students at universities in Saudi Arabia have a positive attitude towards using mobile apps to learn English. The digital literacy practices of college students mostly involved using smartphones and this result is consistent with results by Warni, Abdul Aziz and Febriawan (2018), who mentioned that students in Indonesia use mobile phones in their everyday lives to learn English outside the classroom.…”
Section: Improving Competency In Englishsupporting
confidence: 87%
“…They reported that without it, they were more prone to encounter misunderstandings and get easily puzzled. Indeed, thanks to English online practices and chatting, they could be encouraged by their peers, which has also been investigated in the research of Warni et al (2018). Additionally, they could even widen their circle of friends, as highlighted in the research on using Discord to improve students' conversation skills written by Prasojo et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Students can learn independently and collaborate with a partner thanks to technology. This is achievable because technology fosters critical thinking and analytical thinking in the classroom, two skills that are crucial for the growth of autonomy (Warni, Aziz, & Febriawan, 2018). Education by using information and communication technology such as computers, communication facilities and learning teaching aids and other activities in educational programs Due to their interactive and dynamic nature, ICTs have the capacity to meet demand individual students by giving them the opportunity to focus and broaden their learning knowledge.…”
Section: Introductionmentioning
confidence: 99%